Manejo terapéutico de neumonías en el Área de Neonatología del Hospiotal Isidro Ayora de Loja, periodo 2014. - Guerrero Loaiza, Andrea Yolanda (2016)
A quantitative qualitative and prospective descriptive study, cross-cutting was performed at the Isidro Ayora Loja Hospital in Neonatology area from April to July 2014, with the purpose of knowing the therapeutic management of pneumonia in the area neonatology. The study obtained a sample of 50 infants admitted to the service, diagnosed with respiratory disease. From the results it was determined that the most frequent respiratory morbidities were: 56% of respiratory distress syndrome type I, 22% intrauterine pneumonia, 10% TTN, 8% syndrome meconium aspiration (SAM) and 4% community-acquired pneumonia. Regarding the degree of breathlessness assessed by the score of Downes, 46% of patients had mild respiratory distress, 34% moderate and 20% severe difficulty. The oxygen therapy was used by cephalic oxygen chamber with 46%, 34% used oxygen to continuous positive pressure in the airway (CPAP), and 20% mechanical ventilation. Drug therapy showed greater efficacy was the association of ampicillin - gentamicin at 60%, followed by ampicillin - cefotaxime and ampicillin - amikacin with 20% respectively.The results were summarized in frequency tables and percentages for further analysis and representation in statistical graphics KEYWORDS: pneumonia, Downes score, antibiotics, oxygen therapy.